Molecular Mechanisms Responsible for Mesenchymal Stem Cell-Dependent Attenuation of Tear Hyperosmolarity and Immune Cell-Driven Inflammation in the Eyes of Patients with Dry Eye Disease - Carl Randall Harrell; Valentin Djonov; Ana Volarevic; Aleksandar Arsenijevic; Vladislav Volarevic (Diseases)
Background: Dry eye disease (DED) is a chronic condition characterized by a decrease in tear production or an increase in tear evaporation, leading to inflammation and damage of the ocular surface. Dysfunction of ion channels, tear hyperosmolarity and immune cell-driven inflammation create a vicious circle responsible for the pathological changes in the eyes of DED patients. Mesenchymal stem cells (MSCs) are adult, rapidly proliferating stem cells that produce a large number of immunoregulatory, angiomodulatory, and growth factors that efficiently reduce tear hyperosmolarity-induced pathological changes, inhibit harmful immune response, and provide trophic support to the injured corneal and conjuctival epithelial cells, goblet cells and acinar cells in lacrimal glands of DED patients. Methods: An extensive research in the literature was implemented in order to elucidate the role of MSCs in the attenuation of tear hyperosmolarity and eye inflammation in patients suffering from DED. Results: Findings obtained in preclinical and pilot clinical studies demonstrated that MSCs reduced tear hyperomsolaity-induced pathological changes and suppressed immune cell-driven eye inflammation. Additionally, MSC-based therapy managed to successfully address the most severe DED-related conditions and complications. Conclusions: MSCs should be considered as potentially new therapeutic agents for the treatment of severe DED.